Long-term outcomes of patients with refractory cytopenia of childhood under observation only - Beatrice Drexler; Stephan Schwarz-Furlan; Irith Baumann; Martina Rudelius; Peter Nöllke; Dirk Lebrecht; Senthilkumar Ramamoorthy; Natalia Rotari; Axel Karow; Shinsuke Hirabayashi; Fabian Beier; Yvonne Lisa Behrens; et al. (Blood Advances)
Abstract: Refractory cytopenia of childhood (RCC) describes an entity of well-recognized bone marrow failure defined by persistent cytopenia, dysplastic changes, and a unique histopathological pattern in the bone marrow. Although hematopoietic stem cell transplantation (HSCT) is generally indicated for patients with severe cytopenia or abnormal karyotype, a subset of patients with RCC may be candidates for an observational approach. We evaluated the long-term outcome of patients with RCC without evidence of a genetic predisposition who had a normal karyotype and had not received HSCT or immunosuppressive therapy within 2 years from diagnosis. The median age at diagnosis of the 100 patients analyzed was 10.9 years (range 1.4-17.3); 84% presented with a hypocellular bone marrow. Clonal evolution with abnormal karyotype occurred in 3 patients (3%), and 1 case progressed to myelodysplastic syndrome with excess blasts. Three patients (3%) developed paroxysmal nocturnal hematuria. Overall, 9 patients (9%) received HSCT, and the 5- and 10-year HSCT-free survival was 94% and 88%, respectively. At last follow-up, all patients were alive with a median follow-up time of 7.2 years. These results indicate that an observational approach is safe for selected patients with RCC with a normal karyotype after an exclusion of a germ line predisposition syndrome. However, persistence of cytopenia in most of these patients underscores the importance of long-term surveillance and transition to adult hematology care. This trial was registered at www.clinicaltrials.gov as #NCT00047268 and #NCT00662090.